Eksplorasi Kelayakan Bisnis Desa Wisata Jawai Laut Melalui Rancangan Website â€œPantau Wisataâ€: Apakah Layak? - Noviriani, Eliza; Narti Prihartini; Delyanet (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The objective of this study is to explore the business feasibility of the Jawai Laut tourism village as a follow-up to the design of the tourism village business feasibility website. The urgency of website development as a means of strategic analysis of the financial aspects of the tourism village will be a good choice, because it is expected to make it easier for stakeholders to make decisions in efforts to develop the tourism village. Website development and exploration of business feasibility must be part of virtual tourism and the creative economy to support technological readiness in the future. The findings of this study are based on financial ratio indicators, the majority of calculation results indicate that investment in the Jawai Laut Tourism Village is feasible.